Transformasi Pengembangan Kurikulum Berbasis Outcome dan Prinsip Active Learning Dalam Pembelajaran Kolaboratif - Melkianus Panda Huki; Lulu Nur Fauzyah; Bambang Sumardjoko; Sabar Narimo (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The development of 21st century education demands an elementary school curriculum that is not only oriented to mastering materials, but also to developing critical thinking, collaboration, creativity, and digital literacy competencies. These conditions encourage the need for curriculum transformation that is more adaptive, measurable, and centered on learners. This study aims to examine, analyze, and formulate an effective and contextual integrated curriculum development model through Outcome-Based Education, Active Learning, and Collaborative Learning approaches. The method used is Systematic Literature Review (SLR) with PRISMA procedure through the stages of identification, screening, feasibility assessment, and Article selection. Data sources were obtained from the SINTA and Scopus databases using keywords related to outcome-based curriculum, Active Learning, Collaborative Learning, and basic education in the 2020-2025 range. From the gradual selection process, 257 articles that meet the inclusion criteria were obtained, then analyzed using content analysis and thematic synthesis. The results showed that the integration of the three approaches synergistically increases learning engagement, clarity of competence achievement, critical thinking ability, cooperation, and the quality of learning outcomes of learners, although the implementation is still influenced by teacher readiness, school management support, and availability of resources. The implication of this study confirms the importance of a holistic, flexible, and institutional support-based curriculum development model so that the transformation of learning in elementary schools is effective and sustainable.